FRI0502 Ixekizumab reduces disease activity in active psoriatic arthritis patients who had previous inadequate response to tumour necrosis factor-inhibitors. (15th June 2017) - Coates, LC; Mease, P; Husni, ME; Lespessailles, E; Adams, DH; Benichou, O; Kerr, L; Helliwell, P
Abstract : Background: Psoriatic arthritis (PsA) is a chronic immune-mediated inflammatory disease associated with psoriasis, peripheral arthritis, enthesitis, dactylitis, and spondylitis. Ixekizumab (IXE), a monoclonal high affinity antibody that selectively targets interleukin-17A, has improved disease activity and physical function in bDMARD-naïve patients with active PsA. 1 Herein, results are presented from a phase 3 trial (SPIRIT-P2; NCT02349295 ) with IXE in patients with active PsA and previous inadequate response to tumour necrosis factor-inhibitors (TNF-i). Objectives: To explore the impact of IXE, as assessed by composite endpoints that incorporate multiple disease domains including peripheral arthritis, skin disease, enthesitis, dactylitis, spinal disease, functioning, and global disease assessment, up to 24 weeks (wks). Methods: In this phase 3, multicentre, double-blind study, 363 adult patients with active PsA and a history of inadequate response to TNF-i were randomly assigned at a 1:1:1 ratio to subcutaneous administration of 80-mg IXE either every 4 wks (Q4W; N=122) or every 2 wks (Q2W; N=123) following a 160-mg starting dose at Wk 0 or placebo (PBO; N=118). TNF-i inadequate response was defined as lack of efficacy to one or two TNF-i or intolerance to TNF-i. Response to treatment and disease activity were measured at Wks 12 and 24 by the following composite endpoints: minimal disease activity with skin component measured with the Psoriasis Area and Severity Index (MDA) or the static Physician Global Assessment of psoriasis (mMDA) and Composite Psoriatic Disease Activity Index (CPDAI) as well as traditional measures by Psoriatic Arthritis Response Criteria (PsARC). Treatment comparisons were made by a logistic regression model for categorical data with missing values imputed by nonresponder imputation (NRI); a mixed model for repeated measures analysis was used for continuous data. Results: At Wks 12 and 24, significantly more patients receiving IXEQ4W or IXEQ2W achieved MDA, mMDA, and PsARC compared with patients receiving PBO (Table). Results for MDA were similar to mMDA results within each treatment group at each time point. CPDAI total scores for patients receiving IXEQ4W or IXEQ2W were significantly improved compared with results for patients receiving PBO. Conclusions: Treatment with either IXEQ2W or IXEQ4W provides improvement in disease activity across multiple symptom domains, as measured by various composite endpoints, in patients with active PsA and who had a previous inadequate response to TNF-i. References: Mease P et al. 2017 ARD 76(1):79. Disclosure of Interest: L. Coates Grant/research support from: Abbvie, Janssen, Consultant for: Abbvie, Celgene, Janssen, Sun Pharma, Pfizer, UCB, MSD, Novartis, Eli Lilly and Company, P. Mease Grant/research support from: Abbvie, Amgen, Bristol Myers Squibb, Celgene, Crescendo, Genentech, Janssen, Eli Lilly and Company, Merck, Novartis, Phizer, UCB Pharma, Sun, Consultant for: Abbvie, Amgen, Bristol Myers Squibb, Celgene, Crescendo, Genentech, Janssen, Eli Lilly and Company, Merck, Novartis, Pfizer, UCB Pharma, Sun, Speakers bureau: Abbvie, Amgen, Bristol Myers Squibb, Celgene, Crescendo, Genentech, Janssen, Pfizer, UCB Pharma, M. Husni Consultant for: Eli Lilly and Company, Novartis, Abbvie, Celgene, Bristol Myers Squibb, Amgen, Janssen, and UCB phrama, E. Lespessailles Grant/research support from: Amgen and Eli Lilly and Company, Speakers bureau: Expancience, Novartis and Servier, D. Adams Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, O. Benichou Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, L. Kerr Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, P. Helliwell Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly and Company, Janssen, Merck, Novartis, and UCB